Environmental Temperature and Material Characterisation of Planar Microwave Evanescent Sensors for Environmental Analysis - Lavers, Christopher (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Microwave sensing; Material Characterisation; Waveguide sensing; DSDS23 Poster; DSDS23